2020
DOI: 10.3390/diagnostics11010027
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Fine-Needle Biopsy of Small Solid Pancreatic Lesions Using a Franseen Needle during Endoscopic Ultrasound Examination

Abstract: Background and aim: During endoscopic ultrasound-guided fine needle aspiration biopsy (EUS-FNB), Franseen needles can help collect sufficient tissue to permit histopathological assessment. However, its efficacy might be limited by the size of the targeted lesion. This study aimed to evaluate the feasibility of histopathological assessment of small solid pancreatic lesions using a 22-gauge Franseen needle during EUS-FNB. Methods: This retrospective study evaluated data from all patients who underwent EUS-FNB us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Multivariate analysis confirmed that EUS-FNA has a low diagnostic accuracy for small pancreatic lesions, especially those <5 mm. 20 Similar results were reported by other retrospective cohort studies. 21,22 These studies indicate that the diagnosis of small pancreatic lesions (<10 mm) by EUS-FNA remains challenging.…”
Section: Used a 22gsupporting
confidence: 87%
See 1 more Smart Citation
“…Multivariate analysis confirmed that EUS-FNA has a low diagnostic accuracy for small pancreatic lesions, especially those <5 mm. 20 Similar results were reported by other retrospective cohort studies. 21,22 These studies indicate that the diagnosis of small pancreatic lesions (<10 mm) by EUS-FNA remains challenging.…”
Section: Used a 22gsupporting
confidence: 87%
“…One of the disadvantages of EUS-FNA is its low diagnostic accuracy for small lesions. Takahashi et al 20…”
Section: Consmentioning
confidence: 99%
“…Third, this study excluded both small lesions (<20 mm) and transduodenal puncture routes. We previously reported that lesion size was an independent predictor of histopathological diagnosis accuracy with a 22-gauge Franseen needle using a multivariate analysis [25]. Regarding a transduodenal puncture route, there are several technical issues with the use of a large-caliber 19-gauge needle due to its stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…EUS plays a decisive role in defining GEP-NENs of the gastrointestinal wall, as it provides information on the size, depth of invasion, and local–regional metastases [ 164 ]. The EUS-guided biopsy can also provide a definitive diagnosis and useful information (for example, the evaluation of the nuclear protein Ki-67, which appears to be a proliferative index) for correctly managing this type of lesion [ 165 ]. In addition, the EUS can accurately select the ideal candidates for the endoscopic resection.…”
Section: Diagnosis Staging and Risk Assessmentmentioning
confidence: 99%